Photoresist, photoresist combination product and photoresist patterning method
By using photoacid generators and zirconia nanoparticle film forming resins in photoresist, the problems of poor mechanical properties and slow photolithography forming rate are solved, and high light sensitivity and nanoscale characteristic size are achieved The lithographic pattern reduces costs and broadens the scope of application.
Patent Information
- Application Number
- CN202110987312.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-26
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-08-26
AI Technical Summary
The existing two-photon photoresist has poor mechanical properties, and the processed patterns are prone to collapse, deform and peel off from the substrate during the development process, and the photolithography forming rate is slow, making it difficult for feature size to reach the nanoscale and cost high.
Using photoresist including organic solvents, photoacid generators and zirconia nanoparticle film-forming resins, the agglomeration of zirconia nanoparticles through photoacid generators is used to form solubility differences between exposure and non-exposure zones, and achieve high light sensitivity. Its properties and excellent mechanical properties improve the photolithographic forming rate and pattern accuracy.
It realizes the high light sensitivity and excellent mechanical properties of photoresist, which can improve the processing accuracy of two-photon lithography on nano-level feature sizes, shorten processing time and reduce costs, and is suitable for the field of purple light lithography to ensure pattern fidelity Spend.
Smart Images

Figure CN115903376B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of photoresist technology, and more specifically, to a photoresist, a photoresist combination product, and a method for patterning photoresist. Background Technology
[0002] Photoresist is a core material in the field of micro-nano fabrication, and its development level determines, to a certain extent, the prospects and applications of micro-nano fabrication technology.
[0003] Two-photon photoresists are a special type of photoresist. They can absorb two or more low-energy photons from a lithography beam, triggering a chemical reaction to achieve pattern transfer and imaging. Currently, most commonly used two-photon photoresists are organic polymers with poor mechanical properties. Therefore, polymer structures exposed by two-photon lithography are prone to collapse, deformation, and peeling from the substrate during development, affecting the quality of the final exposed structure. Currently, the feature sizes of patterns fabricated using two-photon lithography are generally at the micrometer or sub-micrometer scale. Furthermore, the biggest drawback of commercially available two-photon photoresists is their slow lithography rate (i.e., lithography scanning rate) (currently, the practically applicable lithography scanning rate is mostly in the μm / s range). -1 The high time cost required for photolithography (at the level of photolithography) results in a very high time cost for photolithography.
[0004] Besides two-photon photoresists, ultraviolet (UV) photoresists are also commonly used. However, short-wavelength UV light (e.g., 193nm or 248nm UV light sources) can cause permanent damage to polymer substrates (such as plastics and rubber). To avoid this problem, long-wavelength UV light (e.g., 365nm UV light sources) or 405nm violet light is typically used in conjunction with the photoresist for photolithography. However, most commercially available photoresists suitable for long-wavelength UV or violet light are purely organic, with limited variety and poor etching resistance, making it difficult to meet the specific needs of micro- and nano-fabrication fields. Summary of the Invention
[0005] Based on this, the present invention provides a photoresist with fast photolithography forming speed and the ability to process pattern feature sizes down to the nanometer level, a photoresist combination product, and a method for photoresist patterning.
[0006] In one aspect, the present invention provides a photoresist comprising an organic solvent, a photoacid generator, and a zirconium oxide nanoparticle film-forming resin, wherein the zirconium oxide nanoparticle film-forming resin is prepared by mixing zirconium propoxide with an unsaturated organic carboxylic acid and heating.
[0007] The photoacid generator can initiate the aggregation of zirconia nanoparticles into film-forming resins and has the structure shown in Formula I and / or Formula II:
[0008]
[0009] R1 to R8 are independently selected from -H, -CH3, methoxy, ethoxy, or hydroxyethoxy.
[0010] In one aspect, the present invention also provides a photoresist combination product, comprising the photoresist and developer described above.
[0011] In another aspect, the present invention provides a method for photoresist patterning, comprising the following steps:
[0012] The photoresist described above is placed on a substrate and dried to form a photoresist film;
[0013] After photolithographic exposure, the photoresist film is placed in the developer described above for development to form a photolithographic pattern.
[0014] This invention reveals that photoacid generators produce acid upon exposure, initiating an aggregation reaction in the zirconia nanoparticle film-forming resin. Therefore, during photolithography, the zirconia nanoparticle film-forming resin in the illuminated areas aggregates and becomes difficult to dissolve in the developer, while the unilluminated areas do not aggregate and are easily soluble in the developer. The significant difference in solubility of the photoresist in the exposed and unexposed areas allows for the formation of photolithographic patterns.
[0015] Furthermore, the photoresist exhibits high photosensitivity and excellent mechanical properties, making it suitable for applications in two-photon lithography (such as 780nm near-infrared light sources), and it also boasts a fast lithography rate, reaching milliseconds. -1 The photoresist exhibits high precision and small feature size, reaching the nanometer scale and even below 50nm, significantly improving the processing accuracy, shortening processing time, reducing costs, and broadening the practical applications of two-photon lithography. This photoresist can also be applied to ultraviolet lithography (such as 405nm ultraviolet light sources), providing a novel photoresist for long-wavelength ultraviolet or violet lithography. Furthermore, the zirconia nanoparticles ensure excellent mechanical properties of the photoresist, preventing collapse and deformation of the lithographic pattern during development and preventing peeling from the substrate, resulting in high pattern fidelity. Attached Figure Description
[0016] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0017] Figure 1 This is a scanning electron microscope image of the two-photon photoresist pattern in Embodiment 1 of the present invention;
[0018] Figure 2 This is a scanning electron microscope image of the two-photon photoresist pattern in Embodiment 2 of the present invention;
[0019] Figure 3 This is a scanning electron microscope image of the two-photon photoresist pattern in Embodiment 3 of the present invention;
[0020] Figure 4 This is a scanning electron microscope image of the two-photon photoresist pattern in Embodiment 4 of the present invention;
[0021] Figure 5 This is a scanning electron microscope image of the two-photon photoresist pattern in Embodiment 5 of the present invention;
[0022] Figure 6 This is a scanning electron microscope image of the two-photon photoresist pattern in Embodiment 6 of the present invention;
[0023] Figure 7 This is a scanning electron microscope image of the two-photon photoresist pattern in Embodiment 7 of the present invention;
[0024] Figure 8 This is a scanning electron microscope image of the two-photon photoresist pattern in Embodiment 8 of the present invention;
[0025] Figure 9 This is a scanning electron microscope image of the two-photon photoresist pattern in Embodiment 9 of the present invention;
[0026] Figure 10 This is a scanning electron microscope image of the two-photon photoresist pattern in Embodiment 10 of the present invention;
[0027] Figure 11 This is a metallographic microscope image of the ultraviolet photoresist pattern in Embodiment 11 of the present invention;
[0028] Figure 12 This is a scanning electron microscope image of the two-photon photoresist pattern in Comparative Example 1 of the present invention;
[0029] Figure 13 This is a scanning electron microscope image of the two-photon photoresist pattern in Comparative Example 2 of the present invention. Detailed Implementation
[0030] Reference will now be made to detailed embodiments of the present invention, one or more of which are described below. Each example is provided for explanation and not for limitation of the invention. In fact, it will be apparent to those skilled in the art that various modifications and variations can be made to the invention without departing from its scope or spirit. For example, features described or illustrated as part of one embodiment may be used in another embodiment to produce further embodiments.
[0031] Therefore, this invention is intended to cover such modifications and variations falling within the scope of the appended claims and their equivalents. Other objects, features, and aspects of the invention are disclosed in or will be apparent from the following detailed description. It will be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0033] Terms and Definitions
[0034] "Purple light" refers to violet visible light, which belongs to the visible light spectrum and has a wavelength of 450nm to 400nm.
[0035] "Ultraviolet photoresist" refers to photoresist that uses ultraviolet light as a light source for photolithography exposure.
[0036] In one aspect, the present invention provides a photoresist comprising an organic solvent, a photoacid generator, and a zirconium oxide nanoparticle film-forming resin, wherein the zirconium oxide nanoparticle film-forming resin is prepared by mixing zirconium propoxide with an unsaturated organic carboxylic acid and heating.
[0037] The photoacid generator can initiate the aggregation of zirconia nanoparticles into film-forming resins and has the structure shown in Formula I and / or Formula II:
[0038]
[0039] R1 to R8 are independently selected from -H, -CH3, methoxy, ethoxy, or hydroxyethoxy.
[0040] In some embodiments, the photoacid generator is one or more of 2,4-bis(trichloromethyl)-6-p-methoxystyryl-S-triazine, 2-(3,4-dimethoxystyryl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(2,4-dimethoxystyryl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-[4-(2-hydroxyethoxy)styryl]-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-[2-(furan-2-yl)vinyl]-4,6-bis(trichloromethyl)-1,3,5-triazine, and 2-[2-(5-methylfuran-2-yl)vinyl]-4,6-bis(trichloromethyl)-1,3,5-triazine.
[0041] The structural formulas are as follows:
[0042]
[0043] In some embodiments, the unsaturated organic carboxylic acid can be acrylic acid, methacrylic acid, or 3,3-dimethacrylic acid.
[0044] In some embodiments, zirconium propoxide can be zirconium isopropoxide or zirconium n-propoxide.
[0045] In some embodiments, the mass percentage of the zirconia nanoparticle film-forming resin is 1% to 20%, and may also be 3%, 5%, 10%, 15%, etc. The mass percentage of the photoacid generator is 0.005% to 3%, and may also be 0.02%, 0.05%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, etc.
[0046] In some embodiments, the volume average particle size of the zirconia nanoparticle film-forming resin is 1 nm to 3 nm. The very small volume average particle size of the zirconia nanoparticle film-forming resin allows for photolithographic patterns with very small feature sizes.
[0047] In some embodiments, the organic solvent is selected from those with strong solubility for the photoacid generator and the zirconia nanoparticle film-forming resin, so that the photoacid generator and the zirconia nanoparticle film-forming resin can be well dissolved and uniformly dispersed in the organic solvent. After the photoresist is placed on the substrate and dried to form a photoresist film, it can be ensured that the photoacid generator and the zirconia nanoparticle film-forming resin can be uniformly dispersed in the photoresist film. After photolithography exposure, the exposed areas of the photoresist are difficult to dissolve in the developer, while the non-exposed areas of the photoresist can dissolve accurately and quickly. Preferably, the organic solvent includes at least one selected from propylene glycol monomethyl ether acetate, acetone, methanol, ethanol, n-propanol, isopropanol, butyl acetate, and ethyl lactate.
[0048] In one aspect, the present invention also provides a photoresist combination product, comprising the photoresist and developer described above.
[0049] The developer is compatible with the photoresist and is used to dissolve the photoresist in non-exposed areas. In some embodiments, the developer includes, but is not limited to, at least one of 1,2-diacetoxypropane, propylene glycol monomethyl ether acetate, p-xylene, m-xylene, o-xylene, toluene, isopropoxyethanol, ethylene glycol propyl ether, isopropanol, propylene glycol butyl ether, propylene glycol ethyl ether, ethyl acetate, and acetone.
[0050] In another aspect, the present invention provides a method for photoresist patterning, comprising the following steps:
[0051] The photoresist described above is placed on a substrate and dried to form a photoresist film;
[0052] After photolithographic exposure, the photoresist film is placed in the developer described above to form a photolithographic pattern.
[0053] In some embodiments, the photoresist can be placed on the substrate using methods and apparatus commonly used in the art, such as a spin coater. The spin coater is controlled to rotate at 500 rpm to 5000 rpm and accelerate at 100 rpm. -1 ~1000rpms -1 Photoresist is applied onto a substrate. Examples of substrates used include, but are not limited to, glass substrates, quartz substrates, and silicon wafer substrates.
[0054] In some embodiments, the step of filtering the photoresist with a filter membrane is included before placing the photoresist on the substrate. The filter membrane can be a conventional small pore size, preferably 0.22 μm.
[0055] In some embodiments, the drying process to form the photoresist film can be performed using conventional methods and apparatus, such as a photoresist drying machine. The temperature of the photoresist drying machine is controlled at 60°C to 100°C to dry the photoresist and form a film.
[0056] In some embodiments, the photolithography method is violet lithography or two-photon lithography. The violet lithography uses violet light with a wavelength of 405 nm as the light source, while the two-photon lithography uses a near-infrared femtosecond pulsed laser with a wavelength of 780 nm, wherein the laser power is 5 mW to 80 mW. The photoresist of this invention is particularly suitable for two-photon lithography.
[0057] The photoresist, photoresist combination product, and photoresist patterning method of the present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0058] Example 1
[0059] The preparation method of the zirconia nanoparticle film-forming resin in this embodiment is as follows: 1g of zirconium isopropoxide and 12mL of methacrylic acid were added to a 50mL flask and heated and stirred at 65℃ for 15min. Then, 2mL of a mixture of methacrylic acid and water (volume ratio 9:1) was added dropwise to the flask, and the mixture was heated and stirred at 65℃ for 18h. Then, another 2mL of the same mixture was added dropwise to the flask, and the mixture was heated and stirred at 65℃ for 3h. The solution was then poured into 60mL of deionized water. After the precipitate formed, the solid precipitate was separated by centrifugation and washed twice with 80mL of deionized water. The precipitate was dissolved in 20mL of acetone and diluted with 20mL of deionized water. After a white solid precipitated, the white solid was washed twice with a mixture of 40mL of acetone and water (volume ratio 1:3) and dried under vacuum at 65℃ for 4h to obtain a white solid powder, i.e., the zirconia nanoparticle film-forming resin.
[0060] 0.02 g of 2,4-bis(trichloromethyl)-6-p-methoxystyryl-S-triazine and 0.5 g of zirconium oxide nanoparticle film-forming resin were dissolved in 9.5 g of propylene glycol monomethyl ether acetate solvent and stirred until completely dissolved. The photoresist solution was then filtered twice using a filter membrane with a pore size of 0.22 μm.
[0061] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a spin coater at a speed of 2000 rpm and an acceleration of 1000 rpm. -1 Spread the adhesive evenly for 1 minute. Then, remove the substrate and place it in a baking oven at 100°C for 1 minute. Next, place the substrate in a two-photon lithography machine, using a 780nm near-infrared femtosecond pulsed laser as the light source, with a laser power of 22.5mW and a 0.9ms pulse duration. -1 Photolithography was performed at a specific scanning rate. After exposure, the substrate was developed in 1,2-diacetoxypropane for 15 seconds, and residual developer was removed from the substrate surface using a nitrogen gun. Finally, a high-resolution scanning electron microscope (SEM) was used to photograph the resulting pattern. The SEM parameters were: accelerating voltage 0.800 kV, working distance 3.7 mm, and magnification 29.74 kΩ. Figure 1 As shown, the measured feature size of the pattern is 48.81 nm, which is rounded to 49 nm.
[0062] Example 2
[0063] The preparation method in this embodiment is basically the same as that in Example 1, except that the laser power and photolithography scanning rate are different. The specific steps are as follows:
[0064] 0.02 g of 2,4-bis(trichloromethyl)-6-p-methoxystyryl-S-triazine and 0.5 g of zirconium oxide nanoparticle film-forming resin were dissolved in 9.5 g of propylene glycol monomethyl ether acetate solvent and stirred until completely dissolved. The photoresist solution was then filtered twice using a filter membrane with a pore size of 0.22 μm.
[0065] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a spin coater at a speed of 2000 rpm and an acceleration of 1000 rpm. -1 Spread the adhesive evenly for 1 minute. Then remove the substrate and place it in a baking oven at 100°C for 1 minute. Next, place the substrate in a two-photon lithography machine, using a 780nm near-infrared femtosecond pulsed laser as the light source, with a laser power of 20mW and a 0.5ms pulse duration. -1 Photolithography was performed at a specific scanning rate. After exposure, the substrate was developed in 1,2-diacetoxypropane for 15 seconds, and residual developer on the substrate surface was dried using a nitrogen gun. Finally, a high-resolution scanning electron microscope (SEM) was used to photograph the pattern obtained from the photolithography exposure. The SEM parameters were: accelerating voltage 0.800 kV, working distance 3.7 mm, and magnification 19.64 kΩ. Figure 2 As shown, the measured feature size of the pattern is 56.85 nm, which is rounded to 57 nm.
[0066] Example 3
[0067] The preparation method in this embodiment is basically the same as that in Example 1, except that the photolithography scanning rate is different. The specific steps are as follows:
[0068] 0.02 g of 2,4-bis(trichloromethyl)-6-p-methoxystyryl-S-triazine and 0.5 g of zirconium oxide nanoparticle film-forming resin were dissolved in 9.5 g of propylene glycol monomethyl ether acetate solvent and stirred until completely dissolved. The photoresist solution was then filtered twice using a filter membrane with a pore size of 0.22 μm.
[0069] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a spin coater at a speed of 2000 rpm and an acceleration of 1000 rpm. -1 Spread the adhesive evenly for 1 minute. Then, remove the substrate and place it in a baking oven at 100°C for 1 minute. Next, place the substrate in a two-photon lithography machine, using a 780nm near-infrared femtosecond pulsed laser as the light source, with a laser power of 22.5mW and a 0.7ms pulse duration. -1Photolithography exposure was performed at a specific scanning rate. After exposure, the substrate was developed in 1,2-diacetoxypropane for 15 seconds, and residual developer on the substrate surface was dried using a nitrogen gun. Finally, a high-resolution scanning electron microscope (SEM) was used to photograph the pattern obtained from the photolithography exposure. The SEM parameters were: accelerating voltage 0.800 kV, working distance 3.7 mm, and magnification 20.45 kΩ. Figure 3 As shown, the measured feature size of the pattern is 76.43 nm, which is rounded to 76 nm.
[0070] Example 4
[0071] The preparation method in this embodiment is basically the same as that in Example 1, except that the laser power and photolithography scanning rate are different. The specific steps are as follows:
[0072] 0.02 g of 2,4-bis(trichloromethyl)-6-p-methoxystyryl-S-triazine and 0.5 g of zirconium oxide nanoparticle film-forming resin were dissolved in 9.5 g of propylene glycol monomethyl ether acetate solvent and stirred until completely dissolved. The photoresist solution was then filtered twice using a filter membrane with a pore size of 0.22 μm.
[0073] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a spin coater at a speed of 2000 rpm and an acceleration of 1000 rpm. -1 Apply a homogenized coating for 1 minute. Then, remove the substrate and place it in a baking oven at 100°C for 1 minute. Next, place the substrate in a two-photon lithography machine, using a 780nm near-infrared femtosecond pulsed laser as the light source, with a laser power of 17.5mW and a 0.3ms pulse duration. -1 Photolithography exposure was performed at a specific scanning rate. After exposure, the substrate was developed in 1,2-diacetoxypropane for 15 seconds, and residual developer on the substrate surface was dried using a nitrogen gun. Finally, a high-resolution scanning electron microscope (SEM) was used to photograph the pattern obtained from the photolithography exposure. The SEM parameters were: accelerating voltage 0.800 kV, working distance 3.7 mm, and magnification 20.03 kΩ. Figure 4 As shown, the measured feature size of the pattern is 117.1 nm, which is rounded to 117 nm.
[0074] Example 5
[0075] The preparation method in this embodiment is basically the same as that in Example 1, except that the laser power and photolithography scanning rate are different. The specific steps are as follows:
[0076] 0.02 g of 2,4-bis(trichloromethyl)-6-p-methoxystyryl-S-triazine and 0.5 g of zirconium oxide nanoparticle film-forming resin were dissolved in 9.5 g of propylene glycol monomethyl ether acetate solvent and stirred until completely dissolved. The photoresist solution was then filtered twice using a filter membrane with a pore size of 0.22 μm.
[0077] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a spin coater at a speed of 2000 rpm and an acceleration of 1000 rpm. -1 Apply a homogenized coating for 1 minute. Then, remove the substrate and place it in a baking oven at 100°C for 1 minute. Next, place the substrate in a two-photon lithography machine, using a 780nm near-infrared femtosecond pulsed laser as the light source, with a laser power of 25mW and a 0.3ms pulse duration. -1 Photolithography was performed at a specific scanning rate. After exposure, the substrate was developed in 1,2-diacetoxypropane for 15 seconds, and residual developer was removed from the substrate surface using a nitrogen gun. Finally, a high-resolution scanning electron microscope (SEM) was used to photograph the resulting pattern. The SEM parameters were: accelerating voltage 0.800 kV, working distance 4.0 mm, and magnification 15.00 kΩ. Figure 5 As shown, the measured feature size of the pattern is 201.0 nm, which is rounded to 201 nm.
[0078] Example 6
[0079] The preparation method in this embodiment is basically the same as that in Example 1, except that the amount of 2,4-bis(trichloromethyl)-6-p-methoxystyryl-S-triazine, the laser power for photolithography, and the photolithography scanning rate are different. The specific steps are as follows:
[0080] 0.05 g of 2,4-bis(trichloromethyl)-6-p-methoxystyryl-S-triazine and 0.5 g of zirconium oxide nanoparticle film-forming resin were dissolved in 9.5 g of propylene glycol monomethyl ether acetate solvent and stirred until completely dissolved. The photoresist solution was then filtered twice using a filter membrane with a pore size of 0.22 μm.
[0081] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a spin coater at a speed of 2000 rpm and an acceleration of 1000 rpm. -1 Spread the adhesive evenly for 1 minute. Then remove the substrate and place it in a baking oven at 100°C for 1 minute. Next, place the substrate in a two-photon lithography machine, using a 780nm wavelength near-infrared femtosecond pulsed laser as the light source, with a laser power of 37.5mW and a wavelength of 2ms. -1Photolithography was performed at a specific scanning rate. After exposure, the substrate was developed in 1,2-diacetoxypropane for 15 seconds, and residual developer was removed from the substrate surface using a nitrogen gun. Finally, a high-resolution scanning electron microscope (SEM) was used to photograph the resulting pattern. The SEM parameters were: accelerating voltage 0.500 kV, working distance 4.6 mm, and magnification 12.51 kΩ. Figure 6 As shown, the feature size of the measured pattern is 220 nm.
[0082] Example 7
[0083] The preparation method in this embodiment is basically the same as that in Example 6, except that the laser power for photolithography is different. The specific steps are as follows:
[0084] 0.05 g of 2,4-bis(trichloromethyl)-6-p-methoxystyryl-S-triazine and 0.5 g of zirconium oxide nanoparticle film-forming resin were dissolved in 9.5 g of propylene glycol monomethyl ether acetate solvent and stirred until completely dissolved. The photoresist solution was then filtered twice using a filter membrane with a pore size of 0.22 μm.
[0085] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a spin coater at a speed of 2000 rpm and an acceleration of 1000 rpm. -1 Spread the adhesive evenly for 1 minute. Then remove the substrate and place it in a baking oven at 100°C for 1 minute. Next, place the substrate in a two-photon lithography machine, using a 780nm wavelength near-infrared femtosecond pulsed laser as the light source, at a laser power of 45mW and a 2ms spectral density. -1 Photolithography exposure was performed at a specific scanning rate. After exposure, the substrate was developed in 1,2-diacetoxypropane for 15 seconds, and residual developer on the substrate surface was dried using a nitrogen gun. Finally, a high-resolution scanning electron microscope (SEM) was used to photograph the pattern obtained from the photolithography exposure. The SEM parameters were: accelerating voltage 0.500 kV, working distance 4.6 mm, and magnification 10.70 kΩ. Figure 7 As shown, the feature size of the measured pattern is 293 nm.
[0086] Example 8
[0087] The preparation method in this embodiment is basically the same as that in Example 1, except that the amount of 2,4-bis(trichloromethyl)-6-p-methoxystyryl-S-triazine, the laser power for photolithography, and the photolithography scanning rate are different. The specific steps are as follows:
[0088] 0.04 g of 2,4-bis(trichloromethyl)-6-p-methoxystyryl-S-triazine and 0.5 g of zirconium oxide nanoparticle film-forming resin were dissolved in 9.5 g of propylene glycol monomethyl ether acetate solvent and stirred until completely dissolved. The photoresist solution was then filtered twice using a filter membrane with a pore size of 0.22 μm.
[0089] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a spin coater at a speed of 2000 rpm and an acceleration of 1000 rpm. -1 Spread the adhesive evenly for 1 minute. Then remove the substrate and place it in a baking oven at 100°C for 1 minute. Next, place the substrate in a two-photon lithography machine, using a 780nm near-infrared femtosecond pulsed laser as the light source, with a laser power of 50mW and a 1.5ms pulse duration. -1 Photolithography exposure was performed at a specific scanning rate. After exposure, the substrate was developed in 1,2-diacetoxypropane for 15 seconds, and residual developer on the substrate surface was dried using a nitrogen gun. Finally, a high-resolution scanning electron microscope (SEM) was used to photograph the pattern obtained from the photolithography exposure. The SEM parameters were: accelerating voltage 0.500 kV, working distance 5.1 mm, and magnification 7.83 kΩ. Figure 8 As shown, the measured feature size of the pattern is 299.3 nm, which is rounded to 299 nm.
[0090] Example 9
[0091] The preparation method in this embodiment is basically the same as that in Example 1, except that the photoacid generator is 2-(3,4-dimethoxystyryl)-4,6-bis(trichloromethyl)-1,3,5-triazine, and the laser power and photolithography scanning rate are different. The specific steps are as follows:
[0092] 0.02 g of 2-(3,4-dimethoxystyryl)-4,6-bis(trichloromethyl)-1,3,5-triazine and 0.5 g of zirconia nanoparticle film-forming resin were dissolved in 9.5 g of propylene glycol monomethyl ether acetate solvent and stirred until completely dissolved. The photoresist solution was then filtered twice through a 0.22 μm pore size filter membrane.
[0093] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a spin coater at a speed of 2000 rpm and an acceleration of 1000 rpm. -1 Spread the adhesive evenly for 1 minute. Then remove the substrate and place it in a baking oven at 100°C for 1 minute. Next, place the substrate in a two-photon lithography machine, using a 780nm near-infrared femtosecond pulsed laser as the light source, with a laser power of 25mW and a 0.1ms pulse duration. -1Photolithography exposure was performed at a specific scanning rate. After exposure, the substrate was developed in 1,2-diacetoxypropane for 15 seconds, and residual developer on the substrate surface was dried using a nitrogen gun. Finally, a high-resolution scanning electron microscope (SEM) was used to photograph the pattern obtained from the photolithography exposure. The SEM parameters were: accelerating voltage 0.800 kV, working distance 4.0 mm, and magnification 49.08 kΩ. Figure 9 As shown, the measured feature size of the pattern is 147.9 nm, which is rounded to 148 nm.
[0094] Example 10
[0095] The preparation method in this embodiment is basically the same as that in Example 1, except that the photoacid generator is 2-[2-(furan-2-yl)vinyl]-4,6-bis(trichloromethyl)-1,3,5-triazine, and the laser power and photolithography scanning rate are different. The specific steps are as follows:
[0096] 0.02 g of 2-[2-(furan-2-yl)vinyl]-4,6-bis(trichloromethyl)-1,3,5-triazine and 0.5 g of zirconia nanoparticle film-forming resin were dissolved in 9.5 g of propylene glycol monomethyl ether acetate solvent and stirred until completely dissolved. The photoresist solution was then filtered twice through a 0.22 μm pore size filter membrane.
[0097] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a spin coater at a speed of 2000 rpm and an acceleration of 1000 rpm. -1 Spread the adhesive evenly for 1 minute. Then, remove the substrate and place it in a baking oven at 100°C for 1 minute. Next, place the substrate in a two-photon lithography machine, using a 780nm wavelength near-infrared femtosecond pulsed laser as the light source, with a laser power of 30mW and a 0.01ms pulse duration. -1 Photolithography exposure was performed at a specific scanning rate. After exposure, the substrate was developed in 1,2-diacetoxypropane for 15 seconds, and residual developer on the substrate surface was dried using a nitrogen gun. Finally, a high-resolution scanning electron microscope (SEM) was used to photograph the pattern obtained from the photolithography exposure. The SEM parameters were: accelerating voltage 0.800 kV, working distance 4.2 mm, and magnification 10.00 k. Figure 10 As shown, the measured feature size of the pattern is 390.8 nm, which is rounded to 391 nm.
[0098] Example 11
[0099] The preparation method in this embodiment is basically the same as that in Example 1, except that the photolithography method is ultraviolet photolithography, and the laser power and scanning rate of the photolithography exposure are different. The specific steps are as follows:
[0100] 0.02 g of 2,4-bis(trichloromethyl)-6-p-methoxystyryl-S-triazine and 0.5 g of zirconium oxide nanoparticle film-forming resin were dissolved in 9.5 g of propylene glycol monomethyl ether acetate solvent and stirred until completely dissolved. The photoresist solution was then filtered twice using a filter membrane with a pore size of 0.22 μm.
[0101] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a spin coater at a speed of 2000 rpm and an acceleration of 1000 rpm. -1 Spread the adhesive evenly for 1 minute. Then remove the substrate and place it in a baking oven at 100°C for 1 minute. Next, place the substrate in a UV lithography machine, using a 405nm wavelength UV laser as the light source, at a laser power of 20mW and a 3ms sm lithography process. -1 Photolithography was performed at a specific scanning rate. After exposure, the substrate was developed in 1,2-diacetoxypropane for 15 seconds, and any residual developer on the substrate surface was dried using a nitrogen gun. Finally, a photograph of the resulting pattern was taken using a metallurgical microscope. Figure 11 As shown, the measured feature size of the pattern is 6.8 μm, indicating that the photoresist prepared in this embodiment is suitable for the field of ultraviolet lithography.
[0102] Comparative Example 1
[0103] The preparation method of this comparative example is basically the same as that of Example 1, except that the photoacid generator is 2-(4-methoxyphenyl)-4,6-bis(trichloromethyl)-S-triazine, and the laser power and photolithography scanning rate are different. The specific steps are as follows:
[0104] 0.02 g of 2-(4-methoxyphenyl)-4,6-bis(trichloromethyl)-S-triazine and 0.5 g of zirconia nanoparticle film-forming resin were dissolved in 9.5 g of propylene glycol monomethyl ether acetate solvent and stirred until completely dissolved. The photoresist solution was then filtered twice using a filter membrane with a pore size of 0.22 μm.
[0105] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a spin coater at a speed of 2000 rpm and an acceleration of 1000 rpm. -1 Spread the adhesive evenly for 1 minute. Then, remove the substrate and place it in a baking oven at 100°C for 1 minute. Next, place the substrate in a two-photon lithography machine, using a 780nm wavelength near-infrared femtosecond pulsed laser as the light source, with a laser power of 30mW and a 0.01ms pulse duration. -1Photolithography was performed at a specific scanning rate. After exposure, the substrate was developed in 1,2-diacetoxypropane for 15 seconds, and residual developer was removed from the substrate surface using a nitrogen gun. Finally, a high-resolution scanning electron microscope (SEM) was used to photograph the resulting pattern. The SEM parameters were: accelerating voltage 0.800 kV, working distance 4.2 mm, and magnification 1.00 k. Figure 12 As shown, no pattern was observed after exposure, indicating that the photoacid generator 2-(4-methoxyphenyl)-4,6-bis(trichloromethyl)-S-triazine is not suitable for the two-photon lithography method described in this invention.
[0106] Comparative Example 2
[0107] The preparation method of this comparative example is basically the same as that of Example 1, except that the photoacid generator is 2-(1,3-benzodioxolane-5-yl)-4,6-bis(trichloromethyl)-1,3,5-triazine, and the laser power and photolithography scanning rate are different. The specific steps are as follows:
[0108] 0.02 g of 2-(1,3-benzodioxolane-5-yl)-4,6-bis(trichloromethyl)-1,3,5-triazine and 0.5 g of zirconia nanoparticle film-forming resin were dissolved in 9.5 g of propylene glycol monomethyl ether acetate solvent and stirred until completely dissolved. The photoresist solution was then filtered twice through a 0.22 μm pore size filter membrane.
[0109] The prepared photoresist solution was dropped onto the surface of a clean glass substrate and placed in a spin coater at a speed of 2000 rpm and an acceleration of 1000 rpm. -1 Spread the adhesive evenly for 1 minute. Then, remove the substrate and place it in a baking oven at 100°C for 1 minute. Next, place the substrate in a two-photon lithography machine, using a 780nm wavelength near-infrared femtosecond pulsed laser as the light source, with a laser power of 30mW and a 0.01ms pulse duration. -1 Photolithography was performed at a specific scanning rate. After exposure, the substrate was developed in 1,2-diacetoxypropane for 15 seconds, and residual developer was removed from the substrate surface using a nitrogen gun. Finally, a high-resolution scanning electron microscope (SEM) was used to photograph the resulting pattern. The SEM parameters were: accelerating voltage 0.800 kV, working distance 4.2 mm, and magnification 1.00 k. Figure 13 As shown, no pattern was observed after exposure, indicating that the photoacid generator 2-(1,3-benzodioxolane-5-yl)-4,6-bis(trichloromethyl)-1,3,5-triazine is not suitable for the two-photon lithography method described in this invention.
[0110] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0111] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A photoresist, characterized in that: The method comprises an organic solvent, a photoacid generator and a zirconium oxide nanoparticle film-forming resin, and zirconium propoxide and an unsaturated organic carboxylic acid are mixed and heated to prepare the zirconium oxide nanoparticle film-forming resin; The photoacid generator can induce the agglomeration of the zirconium oxide nanoparticle film-forming resin and has a structure shown in Formula I and / or Formula II: Formula I, Formula II; Wherein R1~R8 are independently selected from -H, -CH3, methoxy, ethoxy or hydroxyethoxy.
2. The photoresist according to claim 1, characterized in that The photoacid generator is one or more of 2,4-bis(trichloromethyl)-6-p-methoxyphenylvinyl-S-triazine, 2-(3,4-dimethoxyphenylvinyl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(2,4-dimethoxyphenylvinyl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-[4-(2-hydroxyethoxy)phenylvinyl]-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-[2-(furan-2-yl)vinyl]-4,6-bis(trichloromethyl)-1,3,5-triazine and 2-[2-(5-methylfuran-2-yl)vinyl]-4,6-bis(trichloromethyl)-1,3,5-triazine.
3. The photoresist according to claim 1, characterized in that The unsaturated organic carboxylic acid is acrylic acid, methacrylic acid or 3,3-dimethylacrylic acid.
4. The photoresist according to claim 1, characterized in that The mass percentage of the zirconium oxide nanoparticle film-forming resin is 1% to 20%, and the mass percentage of the photoacid generator is 0.005% to 3%.
5. The photoresist according to any one of claims 1 to 4, characterized in that The volume average particle size of the zirconium oxide nanoparticle film-forming resin is 1 nm to 3 nm.
6. The photoresist according to any one of claims 1 to 4, characterized in that The organic solvent includes at least one of propylene glycol monomethyl ether acetate, acetone, methanol, ethanol, n-propanol, isopropanol, butyl acetate and ethyl lactate.
7. A photoresist combination product, characterized in that: The invention comprises the photoresist and the developer as described in any one of claims 1 to 6.
8. The photoresist combination product according to claim 7, characterized in that: The developer includes at least one of 1,2-diacetoxypropane, propylene glycol monomethyl ether acetate, p-xylene, m-xylene, o-xylene, toluene, isopropoxyethanol, ethylene glycol propyl ether, isopropanol, propylene glycol butyl ether, propylene glycol ethyl ether, ethyl acetate and acetone.
9. A method for patterning a photoresist, characterized in that: The following steps are involved: Placing the photoresist according to any one of claims 1 to 6 on a substrate, and drying to form a photoresist film; The photoresist film is exposed to light and then placed in a developer for development to form a photolithographic pattern.
10. The method for patterning photoresist according to claim 9, characterized in that: The photolithography exposure method is ultraviolet light lithography or two-photon lithography.
Citation Information
Patent Citations
Radiation-sensitive composition and pattern-forming method
US20190258162A1